Business Model Canvas Training for High School Students in Malang Raya - Ananda Sabil Hussein; Raditha Hapsari (Journal of Interdisciplinary Socio-Economic and Community Study, 2023)
Indonesia's current entrepreneurship ratio is relatively low compared to other countries, indicating the need for initiatives to encourage entrepreneurial skills among the youth. This research aims to address the need for increased entrepreneurship in Indonesia, particularly among high school students in the Malang Raya region. The implementation of the community service project has successfully provided valuable entrepreneurship training to high school and vocational students, equipping them with essential knowledge and practical applications of entrepreneurship. The comprehensive training material has ignited enthusiasm and cultivated a strong interest among the participants to engage in entrepreneurial activities. By promoting an entrepreneurial mindset and imparting business strategies, including the Business Model Canvas, the training has accelerated students' understanding and education. Future research should explore different pedagogical approaches in entrepreneurship training, conduct longitudinal studies to track students' progress, and address specific challenges faced by high school and vocational students in starting and running their own businesses. By considering these research directions, entrepreneurship education can be further enhanced, leading to more effective training programs and support for young aspiring entrepreneurs in Malang Raya.